Bringing the digital library success factors into the realm of the technology-organization-environment framework. Issue 3 (30th June 2020) - Singeh, Feria Wirba; Abrizah, A.; Kiran, K.
Abstract : Purpose: The purpose of this paper is to describe a new benchmarking framework on the factors that influence digital library (DL) adoption by aligning them with the constructs of DL models to establish the likely critical success factors (CSFs) for DL implementation. Design/methodology/approach: Concept mapping is used to illustrate the relationship between the information systems success model and DL frameworks. Technology organisation and environment (TOE) framework was chosen as the central theme and was mapped with the three DL frameworks reviewed (5S framework; the Zachman Framework for Enterprise Architecture and the DELOS DL reference model) to come up with the likely success dimensions for DLs. A set of possible success factors was assembled from the literature on previous studies relating to factors that are critical to the success of information systems and DLs. The description of each DL potential success factors was finally developed as an item statement with verification from the literature review. Findings: A total of 53 success factors items were assembled from literature represented by the final ten constructs of the CSFs; 16 items characterise DL technology, 13 items denote DL organisation and 24 items symbolise DL environment. Findings show that these factors may be good determinants for an effective implementation of DLs. Research limitations/implications: The outcome can positively influence the implementation of DLs worldwide. Originality/value: This is the first study in library science that incorporates TOE with DL frameworks to come up with the success factors of DL implementation.